Electrochemical sensor for amino acids and glucose based on glassy carbon electrodes modified with multi-walled carbon nanotubes and copper microparticles dispersed in polyethylenimine - Gutierrez, Fabiana Andrea (2016)
This work reports the analytical performance of glassy carbon electrodes (GCE) modified with multi-walled carbon nanotubes (CNT) and copper microparticles dispersed in polyethylenimine (PEI) (GCE/CNT-PEI-Cu) for the quantification of amino acids, albumin and glucose. The best analytical performance was obtained with CNT-PEI-Cu prepared by sonicating for 15.0 min a mixture of 1.0 mg mL-1 PEI, 1.0 mg mL-1 CNT and 3.0 mg mL-1 copper microparticles. In the case of amino acids and albumin, the analytical signals were obtained from the increase of the copper oxidation signal produced as a consequence of the complex formation between Cu(II) and the amino acids. The sensor allowed the highly sensitive (submicromolar levels) and reproducible (3.9%) amperometric quantification of histidine, serine and cysteine at very low potentials (0.000 V) and pH 7.40. Albumin was quantified by Square Wave Voltammetry after 10.0 min interaction at - 0.100 V with detection limits of 1.2 mg mL-1. GCE/CNT-PEI-Cu was also used for the quantification of glucose by amperometry at 0.700 V in a 0.100 M sodium hydroxide solution through the known catalytic activity of copper towards the oxidation of glucose, with highly competitive detection limits (182 nM). GCE/CNT-PEI-Cu was successfully used for the quantification of amino acids and albumin in pharmaceutical products and carbohydrates in beverages.